Crime Danger Management in Iran's Criminal Law and Islam's Legal Instructions - Rezaeian Koochi, Mohammad Reza; Sahragard, Mojtaba; Najafzadeh Shavaki, Ghadir (Journal of History Culture and Art Research, 2017)
Crime danger management is one of the new concepts of the criminal justice domain which has been introduced since the beginning of the 1990s. After the possibility of achievement of the remedial goals of punishments was questioned and the necessity of criminal justice system's expense control was clear, the atmosphere for the appearance of the administrative approaches in criminal justice domain was prepared. In this approach, the crime is considered a common and normal behavior in the society and the criminals are categorized and managed based on the danger rate and the crime repetition possibility. Iran's criminal legislation system, in spite of the lack of the necessary infrastructures for evaluation and management of the crime danger in different rules and regulations, has approached the issue unsystematically. The dangerous state possesses two aspects: the criminal aspect which implies condition produced in the person by the coincidence of the crime factors, and the social compatibility which means one's compatibility and sociability level. But, recently, what inferred from the rules and regulations is the change of the dangerous state concept and act upon this concept in order to manage the crime commitment danger in the different levels of the criminal justice system which intends to manage and control the endangered groups and supply the public security putting aside the diagnosis and treatment of the positivist approach. In Islam's criminal jurisprudence like the other criminal systems, concerning the crime danger management, solutions like increased penalties in case of the reoffending or determining debilitating punishments like execution or life sentence have been predicted.